STUDY COMPARISON OF TRIAXIAL TEST WITH TRUE AND CONVENTIONAL METHOD ON SPECIMEN IN LABORATORY - HANIF TRI MAULANA (NIM : 12113025), MUHAMMAD
On the actual condition in the field, rocks experience different stresses from any direction. Hence, to create a model of the behavior experienced by the rocks on the actual conditions that occur in the field, a research conducted to develop triaxial test on a laboratory scale, called true triaxial test apparatus. True triaxial test apparatus has the ability to apply three components of the principal stresses independently (σ1 ≠ σ2 ≠ σ3). So that through true triaxial testing, more representative results that close to the actual condition in the field is expected. Different values were found on two types of triaxial testing using both Mohr-Colomb or Hoek & Brown criterion of failure. Based on Mohr-Colomb failure criterion, true triaxial method yields lower cohesion value about 0.25% and also lower friction angle value about 45.28% compared to conventional triaxial testing. While based on Hoek & Brown failure criterion, results from true triaxial method has lower σci value about 20.23% and also about 69.28% lower value for mi compared to conventional triaxial testing. Tunnel modelling in Rocscience Phase2 is performed to determine the impact of different values of cohesion and friction angle resulted from both types of triaxial testing on rock mass strength around the tunnel. Cohesion (c) and the friction angle (ϕ) values from the true triaxial test results lower strength factor about 14.48% on tunnel modelling in each viewing angle compared to conventional triaxial test results.